TO THE QUESTION OF THE PROBABILITY OF THE ATTACKMENT OF DAMAGE AS A RESULT OF ATTACK ON THE INFORMATION RESOURCE OF INFORMATION AND TECHNICAL SYSTEMS OF INTERNAL AFFAIRS TYPE "REFUSAL IN SERVICE" - I. V. Alekhin; O. I. Bokova; D. I. Korobkin; E. A. Rogozin (Вестник Дагестанского государственного технического университета: Технические науки, 2019)
Objectives In order to improve the security of departmental information technology systems and the rationality of the financial costs of hardware solutions in such systems, it is advisable to develop a simulation model of the information technology system of an internal affairs authority (ITS ATS) connected to the Internet to determine the likelihood of damage occurring denial of service attacks. Lead and clarify for the ITS ATS a classification of modern-time complex ITS, which will allow identifying possible threats to the ITS information resource ATS based on open federal and departmental regulatory documents in connection with Internet connection. Further development of the ATS ITS model was done in the Anylogic simulation environment, which makes it possible to simulate a denial of service attack on a departmental resource and investigate the likelihood of damage occurring. The expressions from the apparatus of queuing systems are given, which allow modeling the attack and calculating the probability of damage occurrence, which is advisable to use when designing such systems in ATS. Method. Analytical and mathematical modeling using the apparatus of queuing systems. Result. A simulation model of ITS ATS is proposed, which allows to determine the probability of a destructive impact on the departmental resources of such systems. Conclusion. The direction of this study is relevant and requires further development in order to develop a methodology for assessingthe occurrence of damage in ITS ATS.